Bee assemblage in habitats associated with Brassica napus L. - Halinski,Rosana (2015)
ABSTRACTAssessments in agricultural crops indicate that alterations in the landscape adjacent to the crops can result in reduced productivity due to loss or low abundance of pollinating agents. In the canola crop, production is partially dependent on insect pollination. Therefore, knowledge of the faunal diversity within and near crop fields is key for the management of these insects and consequently for the increase in productivity. This study aimed to determine and compare the diversity of bees in habitats associated with canola fields in southern Brazil. Bees were captured in four agricultural areas using pan traps in three habitat classes: (1) flowering canola crop, (2) forest remnant, and (3) grassland vegetation. The highest abundance of bees was observed in the grassland vegetation (50%) and in the flowering canola field (47%). Eight species common to the three habitat classes were recorded, four of which are represented by native social bees. In addition, a single or a few individuals represented species that were exclusive to a specific habitat class; eight species were collected exclusively in the interior of the canola field, 51 in the grassland vegetation, and six in the forest remnant. The majority of the rare species recorded exhibits subsocial or solitary behaviour and inhabit open places. The composition of bee groups differed between the habitats showing the importance of maintaining habitat mosaics with friendly areas for pollinators, which promote the pollination service for canola flowers.